Polylactide-co-glycolic Acid Nanoparticles for Drug Delivery System - Kumar, S. Sathesh (Asian Journal of Pharmaceutics (AJP), 2021)
Novel drug delivery system, an area of present research is used to carry pharmaceutical ingredients to a targeted site of action in a body, without affecting the nature of the drug. Nanoparticles are too small in size; it has a drug size of 10–100 nm due to its drug size a large amount of drug is absorbed through blood. Polylactide-co-glycolic acid (PLGA) is a synthetic polymer; it has several lactic acids in the unit and several glycolic acids in the unit. PLGA is used with the drug for improved bioavailability and it works on the targeted site of action. It is used as a polymer with the drug which is having less half-life period. The PLGA has been approved by the department of FDA. The PLGA nanoparticles are prepared by the nano-emulsion method and nanoprecipitation method. The PLGA- loaded nanoparticles are administered through various routes of administration such as oral, parenteral, nasal, and transdermal. It is used to treat several diseases such as Alzheimer’s, diabetes, and cancer. The evaluation of PLGA nanoparticles has been done with Fourier transform infrared, differential scanning calorimetric, scanning electron microscopy, transmission electron microscopy, etc. PLGA is a biodegradable polymer possessing superiority over other polymers in targeting the disease. This review aims in pooling the nanoparticles prepared using the biodegradable PLGA polymer and its efficiency in targeting the drug.